ANALISIS KEPUASAN PENGGUNA PERPUSTAKAAN STIE CENDEKIA BOJONEGORO - Ahmad Saifurriza Effasa; Dewi Rochmayanti (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2015)
Motivation is an important factor in determining the student's College of their choosing, so does the perception because it is someone's opinion or judgment about an object. This research aims to find out whether the motivation and perception have influence in the students decisions of choosing STIE Cendekia Bojonegoro as their colleges.This research is quantitative research, data obtained by the natural setting is done with observation, questionnaire, and study the documentation. The population in this research is all the students of STIE Cendekia Bojonegoro in 2013/2014. With the number of samples taken as many as 110, with sampling using stratified random sampling.Based on the results of analysis using Structural Equation Modeling can be inferred that motivation has a significant influence on the decision of choosing. Similarly, the perception has a significant influence on the decision of the choosing.